Analysis of the Role of Teachers in the Implementation of the Pancasila Student Profile Strengthening Project at SDN Puncu IV Kediri - Mustikasari , Sevia Dwi; Febrianto, Priyono Tri (Citra Dharma Cindekia, 2025)
This research aimed to determine the role of teachers in implementing the project to strengthen the profile of Pancasila lessons at SDN Puncu IV Kediri. This type of research was descriptive qualitative research. The subjects of this research were class I teachers and class IV teachers. The data collection techniques used were interview, observation, and documentation techniques. The results of the study are: 1) The role of the teacher a motivator, the role of the teacher as a motivator was by providing support to students, 2) The role of the teacher as a guide, namely the teacher guiding students in understanding and working on new projects, 3) The role of the teacher as a role model, namely by providing examples of good behavior to students so that students are inspired to bring up creative ideas within students, 4) The role of teachers as educators, namely educating students in learning, 5) The role of teachers as teachers, namely teachers can develop teaching materials that were appropriate to the material. What was being studied so that it is easy for students to understand the lesson, 6) The role of the teacher as a learning manager, namely the teacher creates teaching modules and teaching materials that were delivered to students, and 7) The role of the teacher administrator, namely the teacher's role as an administrator played a role in recording student attendance and learning outcomes, 8) Barriers to implementing the Profile Strengthening Project Pancasila students (P5) have obstacles, namely limited implementation time due to busy learning agendas and time constraints. Thus, the role of the teacher was very important in motivating teaching and learning activities. So the impact of providing this motivation was that students feel interested and happy to participate in learning activities. It has been carried out well and it was hoped that future teachers will be more optimal in implementing their role.